Adeno-associated viral vectors for gene therapy - Flotte, T. R.; Berns, Kenneth I., 1938- (Laboratory techniques in biochemistry and molecular biology ;, 2005)
Written by well-known experts in the field, this is a timely update on Adeno-associated virus used in gene therapy. The 10 chapters cover gene therapy in specific diseases such as hemophilia, kidney diseases, and disordes of the central nervous system. *Presents a timely update of gene therapy using the adeno-associated virus *Addresses gene therapy used for hemophilia, kidney diseases, and disorders of the central nervous system *Provides practical advance on vector design *Includes balanced treatment of theoretical risks of gene therapy.